Balance-of-payment-constrained growth in unbalanced productive structures: Disregarded terms of trade negative effects - Medici, Florencia (2015)
The aim of this paper is to analyze the relation between foreign asset formation (FAF) and terms of trade (TOT) in countries characterized by having unbalanced productive structures (UPS). For this purpose, we will modify the structuralist thesis about the (overstated) positive effects of a rise in TOT on the balance-of-payment equilibrium GDP growth rate. In the theoretical analysis, we will follow Thirlwall‟s Law and its subsequent modifications. Our main contribution will be to explain and formalize therein the low ?and even null- effects of TOT on Balance of Payment constraints due to the quasi-rent generated in the export sector of an UPS. In the empirical section, to reinforce this idea, we will econometrically show the existence of a significant and positive relationship between TOT and FAE in developing countries.